Small is the New Big - Rees, Kim (O'Reilly Media, Inc., 2011)
While the majority of charts were designed to handle a variety of data, there is a certain novelty of presenting data in a very succinct way. By designing a presentation method restricted to specific data points, we can realize an economy of space and interface.